2014
DOI: 10.1111/risa.12224
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Disproportionate Exposure to Acute and Chronic Pollution Risks: A Case Study in Houston, Texas

Abstract: While environmental justice (EJ) research in the United States has focused primarily on the social distribution of chronic pollution risks, previous empirical studies have not analyzed disparities in exposure to both chronic (long-term) and acute (short-term) pollution in the same study area. Our article addresses this limitation though a case study that compares social inequities in exposure to chronic and acute pollution risks in the Greater Houston Metropolitan Statistical Area, Texas. The study integrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 27 publications
4
69
0
1
Order By: Relevance
“…Those who had experienced intergenerational sociospatial mobility gains were also detached from the Hispanic community. Thus, they felt no attraction to living among other Hispanic people, which reinforced their protection from HAPs, since Hispanic neighborhoods are at disproportionately high risk in Greater Houston (Linder et al, 2008;Chakraborty et al, 2014;Grineski et al, 2014). In contrast, some Hispanic immigrants encountered relatively safe residential environments by making hard tradeoffs with profound consequences for their life situations.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Those who had experienced intergenerational sociospatial mobility gains were also detached from the Hispanic community. Thus, they felt no attraction to living among other Hispanic people, which reinforced their protection from HAPs, since Hispanic neighborhoods are at disproportionately high risk in Greater Houston (Linder et al, 2008;Chakraborty et al, 2014;Grineski et al, 2014). In contrast, some Hispanic immigrants encountered relatively safe residential environments by making hard tradeoffs with profound consequences for their life situations.…”
Section: Discussionmentioning
confidence: 86%
“…Two, regardless of 'which came first', the outcome remains the same: The exposure of disadvantaged racial/ethnic social spaces to toxic pollution and the reproduction of a racist order (Pulido, 1996). Relationships between immigrants and risks from technological hazards have not previously been examined in Greater Houston, but studies have documented environmental injustices faced by Hispanic people (Linder et al, 2008;Chakraborty et al, 2014;Grineski et al, 2014). For example, Linder et al (2008) found that predominately Hispanic neighborhoods were significantly more likely to be at high risk to HAPs than were neighborhoods with few Hispanic residents.…”
Section: Environmental Injustice In Houston Texasmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar results have also been obtained in Canada (Carrier et al 2014;Jerrett et al 2007;Sider et al, 2013), the United Kingdom (Briggs, Abellan, and Fecht 2008;Mitchell 2005;Mitchell and Dorling 2003), New Zealand (Kingham, Pearce, and Zawar-Reza 2007), Germany (Schikowski et al 2008), Finland (Rotko et al 1999), France (Havard et al 2009) and Norway (Naess et al 2007). However, the link between air pollutant levels and the distribution of ethnic or racial groups seems to be less clear, and tends to vary in different geographic contexts (Pastor, Sadd, and Hipp 2001;Ringquist 1997) Grineski et al (2015) and Chakraborty et al (2014) also found that neighborhoods in Houston characterized by a higher presence of Hispanic residents and a lower percentage of homeowners faced a significantly greater exposure to both chronic and acute pollution risks. In Miami, Grineski et al (2013) determined that Cuban and Colombian neighborhoods were affected by a significantly increased cancer risk from vehicular air pollution.…”
Section: Environmental Nuisancesmentioning
confidence: 99%
“…EJ researchers have investigated social inequities in the geographic distribution of many different environmental hazards and disamenities; including hazardous waste facilities (Anderton, Anderson, Oakes, & Fraser, 1994;UCC, 1987), incinerators and landfills (Been, 1994;Liu, 1997), toxic chemical accidents (Chakraborty, Collins, Grineski, Montgomery, & Hernandez, 2014;Elliott, Wang, Lowe, & Kleindorfer, 2004), vehicular air pollution (Chakraborty, 2009;Kingham, Pearce, & Zawar-Reza, 2007), and flooding Grineski et al, 2012;Montgomery & Chakraborty, 2013). However, EJ research on distribution and access to amenities is more limited than that on disamenities.…”
Section: Introductionmentioning
confidence: 99%